2008
DOI: 10.1537/ase.070411
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of deciduous teeth in the samurai and commoner children of early modern Japan

Abstract: The strict class system in place during the Edo (early modern) period in Japan is thought to have encompassed customs that differed between the samurai (ruling class) and commoners. This study found that in samurai children, deciduous caries occurred only in maxillary incisors at 0.5-2 years of age and did not occur in the mandibular incisors and canines at 3-5 years of age. Conversely, in commoner children, deciduous caries occurred in all maxillary teeth and mandibular molars at 0.5-2 years of age and in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…For example, although no apparent regional differences were seen between the early-modern series of main-island Japan and the Ryukyu Islands, as mentioned before, a population with a quite low rate is known from the early-modern Oterayama site in Honshu (Sakura, 1985), and a rate difference between classes was reported from the early-modern Sougenji and Kyomachi sites of northern Kyushu (Oyamada et al, 2004(Oyamada et al, , 2007b. Thus, it is suggested that the rate of dental caries varied among sites or villages in the early-modern period of the Japanese archipelago, due not only to diet but also to other behavioral factors such as oral hygiene.…”
Section: Discussionmentioning
confidence: 83%
“…For example, although no apparent regional differences were seen between the early-modern series of main-island Japan and the Ryukyu Islands, as mentioned before, a population with a quite low rate is known from the early-modern Oterayama site in Honshu (Sakura, 1985), and a rate difference between classes was reported from the early-modern Sougenji and Kyomachi sites of northern Kyushu (Oyamada et al, 2004(Oyamada et al, , 2007b. Thus, it is suggested that the rate of dental caries varied among sites or villages in the early-modern period of the Japanese archipelago, due not only to diet but also to other behavioral factors such as oral hygiene.…”
Section: Discussionmentioning
confidence: 83%
“…As often mentioned, posterior teeth are more affected than anterior teeth, which confirm the differential susceptibility of the molars to be suffering from dental caries (Klein & Palmer, 1941;Oyamada et al, 2008;Saunders et al, 1997). But it is interesting to point out that some individuals are attained by carious lesions on anterior deciduous teeth in both area of Mikulčice.…”
Section: Prevalence Of Dental Cariesmentioning
confidence: 75%
“…Many of the samurai had slick, polished teeth, and wedge-shaped defects, most likely caused by regular brushing. Such a custom of regular tooth brushing might have functioned to prevent dental caries (Oyamada et al, 2004(Oyamada et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%